(untitled) (Linguostylistic Studies, 2021)
The article, using the case study of the materials collected by the authors during direct participation in scientific events and having studied verbal and nonverbal behavior of the participants of congresses, conferences, scientific readings, symposiums, and the like, substantiates the need to develop their scientific communication flexible skills for effective cooperation and presentation of their research findings. Observations have shown that both young and experienced scientists need such skills at all stages of cooperation with the conference organizers. The study has revealed that participants of scientific events ought to demonstrate three groups of skills. Firstly, communicative – to communicate productively with participants and organizers, build relationships with strangers, express their own opinions, behave in terms of etiquette, be responsible for the timeliness and accuracy of performing the tasks; secondly, cognitive – to create multi-genre texts, use digital technologies, manage time, and follow the demands; thirdly, emotional intelligence – academic integrity, resilience, self-organization, self-presentation of oneself as a person and a scientist, and motivation to participate in scientific activities. The findings of this study argue that soft skills play an important role in the personal and professional growth of students, pedagogical and scientific-pedagogical staff. Owing to these skills, participants in scientific meetings can communicate the latest achievements in various fields of research to the scientific community and the public.